Generation Z Employees’ Experiences of Reward and Punishment Systems: A Phenomenological Study at Ninetynine Indo - Sumarno, Sumarno (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to explore the experiences of Generation Z employees regarding the implementation of reward and punishment systems in the retail sector, with a focus on their implications for motivation, job satisfaction, and loyalty. Employing a qualitative phenomenological approach, data were collected through in-depth interviews, participatory observation, and internal documentation involving eight employees at Ninetynine Indo, Serang, Banten. The findings reveal that non-financial rewards, such as public recognition, training certificates, and personal appreciation, have a greater positive impact than purely financial incentives, as they strengthen intrinsic motivation and emotional bonds with the organization. Collective rewards were found to enhance solidarity and teamwork, though their effectiveness is largely influenced by transparency and clarity of assessment criteria. On the other hand, punishment accompanied by constructive guidance serves as a learning instrument, whereas authoritarian punishment without explanation tends to reduce self-confidence and trigger stress. These findings emphasize that Generation Z demands a fair, communicative, and educational management system, in which rewards and punishments function not only as tools of control but also as means of competency development and psychological well-being.